SOCIOLOGY AND ITS CONTRIBUTION TO THE RISE OF THE NOVEL - Dahlan, Dahlan (Elite : English and Literature Journal, 2017)
Abstract This paper elaborates people and and their school who greatly contribute to the development of literary works, particularly novel. Their contributions inspire authors, critics at the development of ideas of literature, some of them such as: Framkfurt school, Avant Garde, and Genetic structuralism and some schools of critique like Neo Marxian ideology Critique and Bordieu. This paper also shows how sociology ideas are successfully applied to the literary works.